Stress; the vulnerability and association with driving performance - Mohd Tamrin, Shamsul Bahri; Saliman, Khairunnisa; Ng, Yee Guan; Mohd Yusoff, Irwan Syah (Science Publications, 2014)
Several factors may contribute to occurrence of road accidents which are human factors, vehicle factor, road factor and environmental factor. There has been recent evidence of a relationship between road accidents and emotional distress as well as fatigue. Monotonous and complex road environments are the road factor that relates to the internal factor within driver. The overall aim of this study was to compare driving stress, fatigue and driving error between complex and monotonous driving. This experimental study was carried out to measure the stress level, fatigue status and driving performance among hundred male drivers (20-59 years) with driving experience more than one year. Cortisol concentration from respondents' saliva was obtained to measure the stress level due to the driving test. Cortisols were measured using Salimetrics cortisol Enzyme Immunoassay kit (ELISA). Fatigue status was measured by using EEG test to the respondents while conducted the simulator driving test. Driving performance was measured based on the recorded data of Running-of-the Roads (RORI) and Large Speed Variation (LSV) index from the simulator system. This study found that there was a significant difference (p<0.05) between cortisol levels, EEG value and driving errors of monotonous and complex driving. Salivary cortisol level was found higher during monotonous driving compared to complex driving. Theta wave which indicates sleepy and fatigue condition was found higher on monotonous driving compared to other brainwaves which is alpha and beta state. RORI and LSV index was higher recorded during driving in complex road environments. The main implications of this study for road safety shows that monotonous driving had significantly induced driving stress and fatigue while complex driving lead to higher driving errors. Human factors and road factors could possibly put drivers in a higher risk to be involved in road accidents.